Comprehensive identification, localization, and validation of innovation measurement indices at the farm level in Iran - Farsani, Elahe Davoodi; Choobchian, Shahla; Naghani, Moslem Shirvani (Frontiers in Sustainable Food Systems, 2024)
Innovation is a fundamental component of agricultural infrastructure, fostering the sector's development and productivity. Innovation indices tailored to the farm level are benchmarks for assessing innovation within this agricultural context. Therefore, this study aims to discover, localize, and validate comprehensive innovation measurement indices at the farm level. A distinguishing feature of this research is its endeavor to discover and validate a comprehensive tool for measuring innovation at the farm level. Notably, there has been no prior research on discovering comprehensive innovation indices at the farm level, marking a novel aspect of this study. The current research is applied in terms of its purpose and falls into the category of mixed research (quantitative and qualitative), as well as exploratory and descriptive research. This study has been conducted in three stages: The first phase involved reviewing existing literature and extracting indices for measuring innovation. In the second phase, a tool was designed specifically to gauge innovation at the farm level. The third phase entailed face and content validation of the identified indices. This validation process was conducted quantitatively and qualitatively through surveys of subject-matter experts in Iran, and by calculating the content validity ratio (CVR) and content validity index (CVI). To measure innovation at the farm level, 90 items across 7 dimensions (education, infrastructure, market sophistication, business sophistication, knowledge and technology outputs, creative outputs, and innovative outputs) were extracted, localized, and developed. According to the results, dimensions such as innovative outputs, education (farmers' education status in technology and innovation), and infrastructure (familiarity, access, and application of Information and Communication Technology ) demonstrated high credibility based on CVR and CVI scores. The innovation assessment indices can help mitigate the challenges associated with evaluating innovation status on farms, thereby enhancing their condition and increasing farmers' profitability. Accurate and reliable data on innovation status empower farmers in market competition and improve economic performance. Attention to innovation and the use of assessment tools can facilitate the attraction of new investors to the agricultural industry. Furthermore, improving agricultural processes through innovative technologies can contribute to the preservation of natural resources and the reduction of environmental pollution.